Mosque Financial Management: Accounting Recording System Analysis - Amalia, Fitri; Syafina, Laylan; Nasution, Yenni Samri Juliati (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Purpose: This research was conducted to analyze whether a quality accounting system can be realized by implementing ISAK 35 and how the ISAK 35 accounting system will be implemented in 2024, focusing on the Mosque. Methodology: This research uses qualitative techniques and data collection through interviews, observations, and documentation. This research was conducted at the Al-Hikmah Delitua Mosque. Finding: The results of this study state that the accounting recording system for financial management of Al-Hikmah Mosque has not implemented an Accounting Recording System Based on the ISAK 35 accounting standard, the recording system is still carried out using simple records, which is recorded when cash comes in and money goes out. Implication: The implications of this study indicate that the implementation of ISAK 35 in the accounting recording system at the Al-Hikmah Delitua Mosque will increase financial transparency and accountability, which can strengthen the congregation's trust in the management of mosque funds. The implementation of this standard will assist in the preparation of more structured financial reports and in accordance with applicable accounting principles. Originality: This study specifically examines budget transparency to increase congregational trust and there is an increase in budget transparency management in mosque managers.